Accelerated methanogenesis from effluents of hydrogen-producing stage in anaerobic digestion by mixed cultures enriched with acetate and nano-sized magnetite particles. (August 2015) - Yang, Zhiman; Xu, Xiaohui; Guo, Rongbo; Fan, Xiaolei; Zhao, Xiaoxian
Highlights: The paddy soil enrichments degrading acetate were obtained via magnetite addition. Magnetite significantly accelerated methane production from acetate. Rhodocyclaceae -related species were selectively enriched with magnetite addition. Enrichments can rapidly convert the effluents of hydrogen-producing stage to methane. Abstract: Potential for paddy soil enrichments obtained in the presence of nano-sized magnetite particles (named as PSEM) to promote methane production from effluents of hydrogen-producing stage in two-stage anaerobic digestion was investigated. The results showed that the addition of magnetite significantly accelerated methane production from acetate in a dose-independent manner. The results from high-throughput sequencing analysis revealed that Rhodocyclaceae -related species were selectively enriched, which were likely the key players for conversion of acetate to methane in PSEM. Compared to the paddy soil enrichments obtained in the absence of magnetite (named as PSEC), the maximum methane production rate in PSEM was significantly higher (1.5–5.5 times higher for the artificial medium and 0.2–1.7 times higher for the effluents). The accelerated methane production from the effluents indicated remarkably application potential of PSEM for improving performance of anaerobic digestion.